2000
DOI: 10.1111/j.1095-8649.2000.tb02135.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure, age and growth of macrourid fish from the upper slope of the Eastern‐Central Mediterranean

Abstract: Hymenocephalus italicus, Nezumia sclerorhynchus and Coelorhynchus coelorhynchus were found in 80, 75 and 69% of trawl hauls carried out between 250 and 750 m on the upper slope of the Ionian Sea. The abundance of H. italicus and N. sclerorhynchus increased with depth while in C. coelorhynchus the highest densities were observed in the uppermost 500 m. In all three grenadiers the average size increased with depth. The populations had a multimodal sizefrequency distribution. In H. italicus adults were generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…Although these authors did not find spawning females, their data on the reproductive period of T. scabrus in the western Mediterranean are in agreement with our data. In contrast, a study conducted in the central Mediterranean Sea found spawning females in August and January(D'Onghia et al 2000), which suggests that the breeding season differs depending on the region. This implies that environmental conditions could play an important role in determining the reproductive processes of this deep-sea species.…”
mentioning
confidence: 75%
“…Although these authors did not find spawning females, their data on the reproductive period of T. scabrus in the western Mediterranean are in agreement with our data. In contrast, a study conducted in the central Mediterranean Sea found spawning females in August and January(D'Onghia et al 2000), which suggests that the breeding season differs depending on the region. This implies that environmental conditions could play an important role in determining the reproductive processes of this deep-sea species.…”
mentioning
confidence: 75%
“…In the Mediterranean, other gadifirm species living in the upper-middle slope can present a continuous reproductive pattern as in Nezumia sclerorhynchus (D'Onghia et al, 1996(D'Onghia et al, , 1999(D'Onghia et al, , 2000, N. aequalis (Massutí et al, 1995) and Hymenocephalus italicus (Massutí et al, 1995;D'Onghia et al, 1996), a quasi-continuous strategy with a reproductive peak as in Coelorhynchus coelorhynchus (Massutí et al, 1995;D'Onghia et al, 1996D'Onghia et al, , 1999, or a seasonal pattern as in Trachyrhynchus trachyrhynchus (D'Onghia, 1996). The lower slope macrourid studied, Coelorhynchus labiatus, has an autumn-winter spawning (Massutí et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Species of the family Macruridae like Hymenocephalus italicus, Nezumia sclerorhynchus, and Coelorhynchus coelorhynchus (D'Onghia et al 2000) and the family Alepocephalidae like A. rostratus (Morales-Nin et al 1996b) spawn quasi-continuously. In all these species the sex ratio is significantly skewed towards females, which tend to have higher proportions of ripe individuals towards the lower boundaries of their depth ranges.…”
Section: Life Cyclesmentioning
confidence: 98%